Handbook of organopalladium chemistry for organic synthesis - Negishi, Ei-ichi 1935-2021; Meijere, A. de (New York Wiley-Interscience, 2002)
This handbook is organized to provide maximum utility to the bench synthetic chemist. The editor is well-known for his work in exploring, developing, and applying organopalladium chemistry and its contributors include over 24 world authorities in the field.
Volume I. Chapter I: Introduction and Background; Chapter II: Palladium Compounds: Stoichiometric Preparation, in situ Generation, and Some Physical and Chemical Properties; Chapter III: Palladium-catalyzed Reactions Involving Reductive Elimination; Chapter IV: Palladium-catalyzed Reactions Involving Carbopalladation; Volume II: Chapter V: Palladium-catalyzed Reactions Involving Nucleophilic Attack on Ligands; Chapter VI: Palladium-catalyzed Carbonylation and other related reactions involving migratory insertion; Chapter VII: Catalytic Hydrogenation and other Palladium-Catalyzed reactions via Hydropalladation, Metallopalladation, and otherrelated Syn Addition Reactions without Carbon-Carbon Bond Formation or Cleavage; Chapter VIII: Palladium-Catalyzed Oxidation Reactions that have not been discussed in Earlier Parts; Chapter IX: Rearrangement and other Miscellaneous Reactions Catalyzed by Palladium; Chapter X: Technological developments in organopalladium Chemistry; References; Index
UP System perpetual contents
Includes bibliographical references and index
Keywords: Organic compounds -- Synthesis -- Handbooks, manuals, etc; Palladium catalysts -- Handbooks, manuals, etc